(untitled) - Moeran, Brian (Berkeley, 1984)
Contents: Lost Innocence is a model case study of a small japanese pottery community on the southern island of kyushu. sarayama (onta) was put on the map by the folk craft movement; today it struggles to stay on the map by preserving the pure uncorrupted virtues by which it got there while simultaneously enjoying the "corruption" of high incomes, individualistic fame, and the seduction of labor-saving machinery
Keywords: Villages,Ngôi làng; Case studies,Nghiên cứu trường hợp; Japan,Nhật Bản